Effect of ZnO Nano Materials on Grinding Surface Finishing - Yogeswaran, Muthusamy; K., Kadirgama; M. M., Rahman; D., Ramasamy; M. M., Noor (Universiti Malaysia Pahang, 2015)
The surface roughness is a variable often used to describe the quality of ground surfaces as well as to evaluate the competitiveness of the overall grinding system. The main study of this paper is a grinding process was performed on the P20 tool steel by changing the grinding conditions, including the depth of cut, the grinding passes, the type of wheel, and the cutting fluid supply in the experiment. The main objective of the study is to investigate the effect of ZnO nanofluid on the grinding surface finishing and wheel wear. The machined surface of selected specimens undergoes SEM to assess the surface integrity. Artificial neural network was used to predict the surface roughness and recognise the trend of the surface roughness. The result showed the reduction of 47 % surface roughness value in grinding with ZnO nanofluid. Neural network predicts accurately and can recognize the roughness trend